2011
DOI: 10.1007/s00436-011-2274-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activities of chloroform and methanol extracts of Buchholzia coriacea Engler seed

Abstract: The anthelmintic potentials of the chloroform and methanol extracts of Buchholzia coriacea Engler seed were investigated. In folklore medicine, B. coriacea (Capparidaceae) is believed to be useful in the treatment of various kinds of ailments and diseases. At doses of 10 mg/kg, 25 mg/kg and 50 mg/kg, the extracts were tested against Eudrilus eugeniae (earthworm) and Bunostomum phlebotomum (cattle hookworm). The extracts exhibited dose-dependent anthelmintic effects on the earthworms and hookworms. The methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, commercially available anthelmintic agents in developing countries are unaffordable; in addition, these agents and their secondary metabolites pose a threat to human health (Cabaret, 2008). These issues reinforced the need to derive safe and cheap anthelmintic agents from plants (Fred-Jaiyesimi et al, 2011). Although Zanthoxylum is a known potential source of anthelmintic agents for traditional Chinese medicine, only a few studies have assessed the anthelmintic activity of Zanthoxylum species (Olounlade et al, 2012).…”
Section: Tablementioning
confidence: 99%
“…However, commercially available anthelmintic agents in developing countries are unaffordable; in addition, these agents and their secondary metabolites pose a threat to human health (Cabaret, 2008). These issues reinforced the need to derive safe and cheap anthelmintic agents from plants (Fred-Jaiyesimi et al, 2011). Although Zanthoxylum is a known potential source of anthelmintic agents for traditional Chinese medicine, only a few studies have assessed the anthelmintic activity of Zanthoxylum species (Olounlade et al, 2012).…”
Section: Tablementioning
confidence: 99%
“…Previous phytochemical analysis has reported the presence of alkaloids, saponins, cardiac glycosides and flavones glycosides (Adisa et al, 2011). Saponins, anthraquinones, alkaloids, cyanogenic glycosides have been observed by Fred-Jaiyesimi et al (2011). Tannins and cardiac glycosides were also reported by Mbata et al (2009) in the seeds of Buchholzia coriacea.…”
Section: Resultsmentioning
confidence: 86%
“…Although the seed has a low protein content of 13% (Ezekiel and Onyeoziri, 2009), its use in hypertension management has been reported (Adisa et al, 2010). Besides, several studies have also reported other health benefits of the seeds (Fred-Jaiyesimi et al, 2011;Adisa et al, 2010;Ezekiel and Onyeoziri, 2009;Ajaiyeoba et al, 2001). However, information is lacking on the specific wonderful cola compounds (proteins, polyphenols, polysaccharides, etc) that are responsible for these bioactivities.…”
Section: Introductionmentioning
confidence: 99%